2021
DOI: 10.1021/acs.est.1c01114
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of a Sanitation Intervention on Environmental Fecal Contamination in a Cluster-Randomized Controlled Trial in Rural Bangladesh

Abstract: Household latrine access generally is not associated with reduced fecal contamination in the environment, but its long-term effectiveness has not been measured. We conducted an environmental assessment nested within the WASH Benefits Bangladesh randomized controlled trial (NCT01590095). We quantified E. coli and fecal coliforms in samples of stored drinking water, child hands, mother hands, soil, and food among a random sample of households from the sanitation and control arms of the tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Interventions providing basic sanitation services might not be able to sufficiently reduce faecal environmental contamination. 96 , 97 , 98 , 99 When considering basic sanitation, there was no evidence that risk of diarrhoea was associated with the level of community coverage ( appendix 2 p 13 ). This finding could be due to how basic sanitation interventions often fail to adequately isolate excreta from the environment and due to human exposures at different stages along the sanitation chain, from containment to emptying, conveyance, treatment, and disposal or reuse.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions providing basic sanitation services might not be able to sufficiently reduce faecal environmental contamination. 96 , 97 , 98 , 99 When considering basic sanitation, there was no evidence that risk of diarrhoea was associated with the level of community coverage ( appendix 2 p 13 ). This finding could be due to how basic sanitation interventions often fail to adequately isolate excreta from the environment and due to human exposures at different stages along the sanitation chain, from containment to emptying, conveyance, treatment, and disposal or reuse.…”
Section: Discussionmentioning
confidence: 99%
“…71 A cluster-randomized trial in rural Bangladesh likewise found scant evidence of reductions in culturable E. coli concentrations from sanitation improvements. 72,73 Latrine provision also did not reduce the prevalence of pathogenic E. coli genes in soil, meaning neither culture-nor molecular-based measurements of soil E. coli were affected. 39 Other recent trials have not assessed intervention impacts on fecal contamination of soil, but several have evaluated contamination of drinking water, with some also testing child hands, food, or fomites.…”
Section: ■ Discussionmentioning
confidence: 91%
“…A cluster-randomized trial in rural Bangladesh likewise found scant evidence of reductions in culturable E. coli concentrations from sanitation improvements. , Latrine provision also did not reduce the prevalence of pathogenic E. coli genes in soil, meaning neither culture- nor molecular-based measurements of soil E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pooled estimates from certain sample types achieved statistical significance, the sheer quantity of information available convincingly demonstrated the lack of a physically meaningful sanitation intervention impacts on ambient fecal contamination. 73 Many have speculated that sanitation's apparent lack of effect may be due in part to animal fecal contamination. 12,22 Animal feces often contain pathogens capable of infecting humans and animal fecal biomass in domestic environments is estimated to far exceed that from humans.…”
Section: Discussionmentioning
confidence: 99%